Longitudinal associations between neuropsychological functioning and medical responsibility in youth with spina bifida: The moderational role of parenting behaviors. Issue 8 (16th November 2020) - Stern, Alexa; Winning, Adrien; Ohanian, Diana; Driscoll, Colleen F. Bechtel; Starnes, Meredith; Glownia, Karen; Holmbeck, Grayson N.
ABSTRACT: For youth with spina bifida (SB), the transfer of medical responsibilities from parent- to self-management is an important component of autonomy development. Youth with SB are at risk for neurocognitive impairments with inattention and executive dysfunction, which may impact their ability to take responsibility for medical tasks. However, adaptive parenting may buffer against the negative impact of executive/attentional dysfunction on levels of medical responsibility. Thus, this study examined the moderating roles of parenting behaviors and child age on the longitudinal associations between neuropsychological functioning and medical responsibility in youth with SB. Participants were recruited as part of a larger, longitudinal study. Youth with SB ( N = 89, M age  = 11.10 years) completed a neuropsychological battery of executive functioning and attention measures at Time 1 (T1). Parents reported on youth's executive functioning/attention skills at T1, and child medical responsibility two years later at Time 2 (T2). Observational methods were used to assess parenting behaviors (warmth, behavioral and psychological control) at T1. Attention and cognitive shifting skills at T1 were positively related to child medical responsibility at T2. Two-way interactions between planning/organizing skills and paternal acceptance, and planning/organizing skills and paternal psychological control, were found. A three-way interaction between cognitive shifting skills, maternal acceptance, and child age was found. When conceptualizing risk factors for low medical responsibility in youth with SB, it is important to consider the family context beyond individual, cognitive factors. The results are discussed within the wider context of social-ecological models of medical responsibility.